Village Activity Management Information System with Mobile-Responsive User Interface Design and Usability Test - Fahmi Kurniawan; Randi Rian Putra; Cendra Wadisman (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The village is a small part of the city that manages and regulates the governance system in a smaller scope. In carrying out its work, the village has structured activities in realizing the results of these activities. Village activities include several parts. Activities are often carried out in the village both related to the village office, employees and activities related to the community. So that village activities can be monitored properly and can also be seen directly by the community, this activity needs to be informed to the community through an information system or website that can be accessed directly by the wider community. The current village activity management system still uses a manual system and is not optimal. This research aims to build a village activity management information system design that is responsive to mobile which can provide information about activities carried out through the village office to the general public who live around the village or in other areas. Activity information will be managed by the village office admin directly so that they can read or follow up on feedback given by the community on village activities that have been, are being or will be taking place. The information system that is built is expected to be able to assist the village office in carrying out existing activities in the village of Klambir Lima Gardens so that it can be carried out to improve the quality of subsequent activities